Brands and competing factors in purchasing hand phones in the Malaysian market - Rahman, Mahfuzur; Ismail, Yusof; Albaity, Mohamed; Isa, Che Ruhana (Korea Distribution Science Association, 2017)
Hand phones are standard paraphernalia among university students. Factors that motivate them to own the gadget would be of interest to both the students as well as marketers. Hand phone usage is an unexamined field in academic literature, this exploratory study attempts to investigate student purchasing motives in cellular phone markets. It also intends to know the student’s satisfaction with the different services and its future impact on socio economic changes. In this study, undergraduates (n=336) were requested to specify their purchase criteria of hand phone. The instrument used in the study to collect feedback from the respondents contains a combination of open-ended and scaled questions, and some background demographics. The study employed content analysis, Pearson’s correlation, and t-tests as the primary tools to analyze the responses. Results show that brand was rated as the most important factor in student purchase decisions. Other factors, arranged in decreasing order of importance comprise price, product quality, features, durability, availability, promotion, and post purchase service. Brand and price correlated significantly. It is also observed that there is very little difference regarding preference between brand and price in purchasing a hand phone. Marketers may formulate suitable strategies out of the findings to promote hand phones to university undergraduates in Malaysia by emphasizing at brands and price.